Quantifying the Association Between Obesity and In-Hospital Outcomes in Adult Scoliosis Surgery: A Nationwide Inpatient Sample Analysis (2016–2021) - Oded Rabau; Ahmad Essa; Yossi Smorgick; Yoram Anekstein; Jonathan Persitz; Anan Shtewe; Amr Mansour; Saleem Samara; Mohammad Haj Yahya; Eyal Behrbalk (Journal of Clinical Medicine, 2026)
Background/Objectives: To quantify the adjusted association of obesity with in-hospital outcomes in adult scoliosis hospitalizations involving spine deformity corrective surgery. Methods: A retrospective cohort study was conducted using the National Inpatient Sample (2016–2021), including adult hospitalizations for scoliosis undergoing corrective spine surgery. Obesity was the primary exposure. The primary outcome was a composite of in-hospital complications. Secondary outcomes included individual complications, length of stay, total hospital charges, and discharge disposition. Weighted multivariable regression models adjusted for patient- and hospital-level factors were used. Sensitivity analysis was performed excluding severity adjustment to assess potential overadjustment, as the All Patient Refined Diagnosis Related Group (APR-DRG) severity score may partially reflect in-hospital complications. Results: Among 9323 unweighted hospitalizations (representing a national estimate of 46,610 weighted hospitalizations) included (16.6% obese), obesity was associated with a 22% increase in the odds of total in-hospital complications (Odds Ratio (OR) 1.22; 95% Confidence Interval (CI) 1.04–1.43). Among individual complication categories, obesity was associated with higher odds of renal complications (OR 1.69; 95% CI 1.29–2.21), whereas no significant differences were observed in pulmonary, cardiac, Venous Thromboembolism (VTE), or sepsis complications. Additionally, obesity was associated with increased odds of non-home discharge (OR 1.28; 95% CI 1.12–1.46). In sensitivity analysis, these associations were more pronounced, with additional complication categories reaching statistical significance. Conclusions: Obesity is associated with increased in-hospital morbidity in adult scoliosis surgery, particularly higher odds of renal complications and non-home discharge. These population-level findings help optimize preoperative risk communication and anticipate post-acute discharge resource needs.